Design of Rectangular Optical Waveguide on LiTaO3 Crystal Using Thermal Annealled Proton Exchange Methods - Yusuf Nur Wijayanto; Dadin Mahmudin; Pamungkas Daud (Jurnal Elektronika dan Telekomunikasi, 2014)
Optical waveguides are the key component for distributing optical signals with very low propagation loss in optical communication. Several type optical waveguides are established currently such as silica optical fiber. In the planar structure, planar optical waveguides are suitable for implementing to integrated optic applications. In here, rectangular optical waveguides on a planar structure with a LiTaO3 crystal as the substrate are described. The optical waveguides were designed for single mode operation at infrared optical wavelength. The Marcatili method is used for designing by separated the rectangular optical waveguides into two slab optical waveguides. Design rules for the rectangular optical waveguides are discussed in this paper